Analysis of Campus Environment, Curriculum Evaluation, Managerial Support and Professional Skills on Higher Education Quality: The Case of Mongolia - Terguuntsetseg, Rentsendorj (Advances in Social Sciences Research Journal, 2025)
The aim of our study to examined how four major dimensions—campus environment, curriculum evaluation, managerial support, and professional skills of academic staff—influence the perceived and actual education quality within Mongolian universities. The research compares public and private institutions to identify similarities and differences in their approaches to maintaining and improving academic standards. By integrating theoretical foundations such as the Input–Process–Output (IPO) model, Total Quality Management (TQM) in education, and Human Capital Theory, the study explores how supportive management, well-trained teachers, modern facilities, and continuous curriculum evaluation collectively enhance teaching effectiveness, student satisfaction, and institutional performance. The findings are expected to provide evidence-based insights for policymakers, educational leaders, and accreditation bodies to strengthen Mongolia’s higher education system and ensure sustainable improvement in education quality across both public and private sectors.